Craspedacusta sowerbii Lankester 1880 - Calder, Dale R. (Zenodo, 2010)
Craspedacusta sowerbii Lankester, 1880 Fig. 48 Craspedacusta sowerbii Lankester, 1880: 148. Craspedacusta sowerbyi .— Edmondson, 1940: 314 [medusa only].— Matthews, 1963: 18, figs. 1, 2; 1966: 246, figs. 1–5. Type locality. UK: London, Regent’s Park, “…in the tank in the water-lily house…” (Lankester 1880: 147). Material examined. None. Description. As for diagnosis of genus. Remarks. Craspedacusta sowerbii Lankester, 1880 is a well-known freshwater species with a wide geographic range (Kramp 1961; Dumont 1994). Edmondson (1940) first reported the species from Hawaii, based on medusae found at Maliko Gulch, Maui. Both medusa and polyp stages were later reported from Honolulu in aquaria by Matthews (1963, 1966). No specimens of the hydroid were found in collections at the Bishop Museum, and it is not currently known to occur in limnic aquaria and culture systems at the Waikiki Aquarium (Gerald Crow & Kelley Lam, pers. comm., 30 July 2009). A review of the global distribution, dispersal, and feeding ecology of C. sowerbii and other freshwater medusae is given by Dumont (1994). Reported distribution. Hawaii. Maui: Maliko Gulch [medusa only] (Edmondson 1940).–Oahu: Honolulu, in aquaria (Matthews 1963, 1966). Worldwide. All continents except Antarctica, in shallow subtropical and temperate fresh waters (Kramp 1961; Dumont 1994; Jankowski 2001; Jankowski et al. 2008; Zhang et al . 2009). Published as part of Calder, Dale R., 2010, Some anthoathecate hydroids and limnopolyps (Cnidaria, Hydrozoa) from the Hawaiian archipelago 2590, pp. 1-91 in Zootaxa 2590 (1) on page 74, DOI:10.11646/zootaxa.2590.1.1, http://zenodo.org/record/10834110